Proof-of-concept model for instantaneous heart rate-drift correction during low and high exercise exertion - Papini, Gabriele B.; Bonomi, Alberto G.; Sartor, Francesco (Frontiers in Physiology, 2024)
This study aimed at modeling below and above anaerobic threshold exercise-induced heart rate (HR) drift, so that corrected HR could better represent VO 2 kinetics during and after the exercise itself. Fifteen healthy subjects (age: 28 ± 5 years; VO 2 M ax : 50 ± 8 ml/kg/min; 5 females) underwent a maximal and a 30 minutes submaximal (80% of the anaerobic threshold) running exercises. A five-stage computational (i.e., delay block, new training impulse calculation block, Sigmoid correction block, increase block and decrease block) model was built to account for instantaneous HR, fitness and age; and to onset, increase and decrease according to the exercise intensity and duration. The area under the curve (AUC) of the hysteresis function which described the differences in maximal and submaximal exercise-induced VO 2 and HR kinetics was significantly reduced both for maximal (26%) and submaximal (77%) exercises and consequent recoveries. In conclusion, this model allowed HR drift instantaneous correction, which could be exploited in the future for more accurate VO 2 estimations.